REGULATORY MODEL FOR THE UTILIZATION OF LAND BANK MECHANISMS IN INDONESIA TO PREVENT AND AVOID LAND MAFIA PRACTICES: A COMPARATIVE STUDY BASED ON LAND GOVERNANCE - Putri Purbasari R.M.; Delarosa, Stella (Jurnal Paradigma Hukum Pembangunan, 2025)
The issue of the "Land Mafia" in Indonesia reflects legal uncertainty and structural inequality in land ownership. The establishment of the Land Bank Agency through Law Number 6 of 2023 concerning the Stipulation of Government Regulation, instead of Law Number 2 of 2022 concerning Job Creation and Government Regulation Number 64 of 2021, is a government effort to address this issue. However, the existence of this agency has sparked public concerns about the potential for abuse of authority and the return of discriminatory legalistic practices, similar to the principle ofdomain declaration, as revealed in the case of farmers in Konawe, Southeast Sulawesi.1The main problem faced is the absence of a holistic, transparent, and accountable regulatory model that can guarantee that the Land Bank truly functions for the greatest prosperity of the people, not for the interests of certain groups. This study aims to analyze, compare, and formulate a more effective manual regulation of the Land Bank. The research method used is normative juridical with a comparative approach to the Land Bank models in the Netherlands and France. The comparison shows fundamental differences: Indonesia applies a centralized model, while the Netherlands uses a decentralized model integrated with spatial planning, and France operates a semi-private hybrid model (SAFER) that has preferential rights and is supervised by a multi-stakeholder committee.1These findings highlight the advantages of the Dutch model, namely its adaptation to local contexts and efficiency in land consolidation, and the French model, which offers operational efficiency and robust oversight mechanisms. Based on these findings, this report proposes a "Hybrid-Decentralized Land Bank Regulatory Model." This model combines Dutch-style decentralization principles with a French-style multi-stakeholder oversight structure, grounded in fundamental theories of good governance. The success of Land Banks in Indonesia ultimately depends on institutional reforms that ensure transparency, accountability, and public participation, going beyond the mere formulation of formal regulations.